2014 IEEE International Conference on Multimedia and Expo (ICME) 2014
DOI: 10.1109/icme.2014.6890243
|View full text |Cite
|
Sign up to set email alerts
|

Free-viewpoint AR human-motion reenactment based on a single RGB-D video stream

Abstract: When observing a person (an actor) performing or demonstrating some activity for the purpose of learning the action, it is best for the viewers to be present at the same time and place as the actor. Otherwise, a video must be recorded. However, conventional video only provides two-dimensional (2D) motion, which lacks the original third dimension of motion. In the presence of some ambiguity, it may be hard for the viewer to comprehend the action with only two dimensions, making it harder to learn the action. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…We show that by viewing the AR reenactments, users are more easily able to comprehend ambiguous poses. We also subjectively survey the visual quality of the synthesized reenactment, as well as its applicability, and compare it to our previous work [9]. We found that while the visual quality is not at the level of standard video, it is much improved, and is enough to be easily comprehensible.…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…We show that by viewing the AR reenactments, users are more easily able to comprehend ambiguous poses. We also subjectively survey the visual quality of the synthesized reenactment, as well as its applicability, and compare it to our previous work [9]. We found that while the visual quality is not at the level of standard video, it is much improved, and is enough to be easily comprehensible.…”
Section: Introductionmentioning
confidence: 91%
“…Our previous system [9] uses a model-based approach as well, using a cylinder as each body part instead of its detailed shape model. In this article, we newly [18] to obtain a body model in order to increase the quality of the output.…”
Section: Novel View Synthesismentioning
confidence: 99%
See 3 more Smart Citations